Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Konsumen Pada Toko Grosir Shanur Putra Tunggal Tanetea Kab.Gowa: Kualitas Produk, Harga Promosi - Nurul Ilmianih; Buyung Romadhoni; Syarthini Indrayani (BJRM (Bongaya Journal of Research in Management), 2024)
Abstract: This research is quantitative with the aim of knowing the influence of Product Quality, Price, and Promotion on Consumer Purchase Decisions at Shanur Putra Tunggal Wholesale Store, Tanetea, Gowa Regency. The sample was taken from Shanur Putra Tunggal Wholesale Store, Tanetea, Gowa Regency. The type of data used in this study is quantitative data obtained from questionnaires; the data sources used for data collection include primary and secondary data. The sampling technique in this study uses purposive sampling with a total of 120 samples that meet the criteria. The research instrument used in this study employs the Likert scale method. Based on the results of the study data using statistical calculations through the Statistical Package for the Social Sciences (SPSS) Version 30 regarding the Influence of Product Quality, Price, and Promotion on Consumer Purchase Decisions at Shanur Putra Tunggal Wholesale Store, Tanetea, Gowa Regency. Keywords: Product Quality, Price, Promotion, Purchase Decisions.